Characterization of low temperature metallic magnetic calorimeters having gold absorbers with implanted 163Ho ions - Gastaldo, Loredana; Ranitzsch, Philipp; Von Seggern, Falk; Porst, Jan-Patrick; Schäfer, Sönke; Pies, Christian; Kempf, Sebastian; Wolf, Thomas; Fleischmann, Andreas; Enss, Christian; Herlert, Alexander; Johnston, K. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
For the first time we have investigated the behavior of fully micro-fabricated low temperature metallic magnetic calorimeters (MMCs) after undergoing an ion-implantation process. This experiment had the aim to show the possibility to perform a high precision calorimetric measurement of the energy spectrum following the electron capture of 163Ho using MMCs having the radioactive 163Ho ions implanted in the absorber. The isotope 163Ho decays through electron capture to 163Dy and features the smallest known QEC value. This peculiarity makes 163Ho a very interesting candidate to investigate the value of the electron neutrino mass by the analysis of the energy spectrum. The implantation of 163Ho ions was performed at ISOLDE-CERN. The performance of a detector that underwent an ion-implantation process is compared to the one of a detector without implanted ions. The results show that the implantation dose of ions used in this experiment does not compromise the properties of the detector. Moreover the performance of the detector prototype having the 163Ho ions implanted in the absorber is already close to the requirements needed for an experiment with sub-eV sensitivity to the electron neutrino mass. Based on these results, an optimized detector design for future 163Ho experiments is presented.
Gesehen am 27.01.2020
Im Titel ist die Zahl "163" hochgestellt